Microglandular Carcinoma of the Pancreas: A Case Report - Moletta, Lucia; Milanetto, Anna Caterina; Liço, Valbona; Alaggio, Rita; Sperti, Cosimo; Pedrazzoli, Sergio; Pasquali, Claudio (JOP. Journal of the Pancreas, 2012)
Context Microadenocarcinoma (MA) of the pancreas is a rare kind of neoplasm. The term microadenocarcinoma was first proposed for a subtype of pancreatic carcinoma by Cubilla and Fitzgerald in 1975 based largely on the morphological features: small crowded microglandular structures, forming a cribriform pattern, sometimes solid sheets. The status of microadenocarcinoma as an independent tumor entity is still a matter of controversy. We present a case of microglandular carcinoma of the pancreatic head. Case report A 77-year-old man was observed in our department for dyspepsia and important loss of weight. He underwent an abdominal ultrasound which showed a pancreatic head mass of 5.0x5.5 cm. CA 19-9 was 46,300 U/L (reference range: 0-37 U/L). The patient underwent also a CT scan and MRI which confirmed the pancreatic head mass. A 18F-fluorodeoxyglucose positron emission tomography showed a pathological uptake of the tracer in an area of 5 cm, corresponding to the pancreatic head, with a maximum SUV of 3.0. The patient underwent a pancreaticoduodenectomy with a Traverso-Longmire reconstruction. The postoperative course was uneventful. Histology revealed a microglandular carcinoma of the pancreatic head with ductal and acinar differentiation. The tumor size was 6.5x5.0 cm, the MIB1 was 70%. The immunohistochemical study showed positive staining of the neoplastic cells with CAM 5.2 antibodies and negative staining with a battery of neuroendocrine-related markers. The patient underwent chemotherapy with gemcitabine. He died of progression of disease 55 months after surgery. Conclusion MA is a rare pancreatic neoplasia. The main importance of recognizing this rare variant of pancreatic carcinoma lies in avoiding misdiagnosis with other primary and metastatic neuroendocrine neoplasms. Immunohistochemical studies will be of value in such cases for differential diagnosis.